2014
DOI: 10.3390/ijerph110707001
|View full text |Cite
|
Sign up to set email alerts
|

First Year Growth in Relation to Prenatal Exposure to Endocrine Disruptors — A Dutch Prospective Cohort Study

Abstract: Growth in the first year of life may already be predictive of obesity later in childhood. The objective was to assess the association between prenatal exposure to various endocrine disrupting chemicals (EDCs) and child growth during the first year. Dichloro-diphenyldichloroethylene (DDE), mono(2-ethyl-5-carboxypentyl)phthalate (MECPP), mono(2-ethyl-5-hydroxyhexyl)phthalate (MEHHP), mono(2-ethyl-5-oxohexyl)phthalate (MEOHP), polychlorinated biphenyl-153, perfluorooctanesulfonic acid, and perfluoro-octanoic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 49 publications
3
51
0
8
Order By: Relevance
“…Fifteen of 24 studies that investigated DDE exposures found positive associations between prenatal and early exposure to DDE and measures of obesity including BMI (189) (402) (414) (265) (189) (95) (423), weight (174) (189) (127), overweight (21, 408), rapid growth (265) (407), and waist circumference (383, 402) (101, 423). Only one 4-year study on Russian boys aged 6–8 years found a negative association between DDE and BMI (58).…”
Section: Associations Between Pop Exposures and The Development Of Obmentioning
confidence: 99%
“…Fifteen of 24 studies that investigated DDE exposures found positive associations between prenatal and early exposure to DDE and measures of obesity including BMI (189) (402) (414) (265) (189) (95) (423), weight (174) (189) (127), overweight (21, 408), rapid growth (265) (407), and waist circumference (383, 402) (101, 423). Only one 4-year study on Russian boys aged 6–8 years found a negative association between DDE and BMI (58).…”
Section: Associations Between Pop Exposures and The Development Of Obmentioning
confidence: 99%
“…This is surprising given the increasing prevalence and concern with this outcome, as well as numerous studies documenting independent effects of both psychosocial and environmental exposures, and clear patterning of childhood obesity according to SES [54]. For example, recent evidence points to multiple chemical exposures, and to prenatal exposure to endocrinedisrupting chemicals in particular, as factors that may disrupt child growth and contribute to obesity risk [55][56][57]. Likewise, childhood obesity is associated with many sociodemographic risks like growing up in poverty and living with a single parent [58], as well as with experiencing significant psychosocial adversity like maltreatment [4].…”
Section: Discussionmentioning
confidence: 98%
“…Similar studies investigating other organochlorine chemicals with hormonal activities have reported an increase in BMI or risk of overweight associated with prenatal DDT/ DDE exposure at different ages (from 14 months to 6.5 years) (Mendez et al, 2011;Valvi et al, 2014Valvi et al, , 2012Verhulst et al, 2009). However, one study reported a decrease in BMI (de Cock et al, 2014a(de Cock et al, , 2014b and several reported an absence of association (Cupul-Uicab et al, 2013;Garced et al, 2012;Gladen et al, 2004;Warner et al, 2013). Reported associations between prenatal exposure to PCBs and BMI at different ages, from three to seven years, were inconsistent (Dallaire et al, 2014;Tang-Péronard et al, 2014;Valvi et al, 2012;Verhulst et al, 2009).…”
Section: Discussionmentioning
confidence: 89%